Perancangan Sistem Informasi Penjualan Rumah Berbasis Website Pada PT Griya Indah Persada Tangerang Selatan - Sarpudin; Deanna Durbin Hutagalung (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
PT. Griya Indah Persada is one of the companies engaged in the home sales industry located in the city of South Tangerang. The absence of information systems in sales management becomes an obstacle that companies have in carrying out the sale of their units. And the lack of media in doing marketing makes the information obtained by consumers to be not maximal. To overcome this problem requires an information system that can be accessed by employees to manage the sale of their units and also a website application that can be accessed by prospective consumers to get information about housing units to be sold. To that end, a web-based home sales information system was developed using Hypertext Preprocessor (PHP), bootstrapping frameworks and MySQL databases with the aim of providing convenience for employees in carrying out sales transaction management activities in the process of ordering a home by consumers, and also provide convenience for prospective consumers in finding home information that will be purchased in this company. These research stages include analysis of ongoing systems, analasis of proposed systems, system design, implementation and testing. Home sales information system PT. Griya Indah Persada is tested with white box and black box methods with a success rate of 98% in the process of use by employees or consumers with an easy-to-understand website interface.